The Soundtrack of Dissent: Analyzing the Cultural Polarization of 1960s America through Antiwar and Pro-War Protest Movements - Trivino, Christine (University of Waterloo, 2025)
The Vietnam War was a seminal event that perpetuated shifting notions of American culture in a period of significant societal transformation. Its influence extends far beyond the 1960s, providing a foundational context for the evolution of cultural and political discourse in subsequent decades. The cultural dimensions of the Vietnam War are frequently underexamined, despite the numerous cultural contributions that emerged in response to the conflict. Notably, music became a powerful tool for articulating dissent, shaping American society during the era, and mobilizing a generation of young people toward activism. This thesis examines the cultural conflicts in the 1960s and early 1970s, focusing particularly on their relationship to the Vietnam War. It examines both the antiwar and pro-war movements, analyzing their roles in shaping the broader cultural and ideological divisions of the era – a type of phenomenon that could properly be considered a precursor to the modern culture wars of the late 20th and early 21st centuries. Through an in-depth examination of music, youth social movements, and the prevailing narratives of Vietnam War dissent, this study seeks to understand the underlying causes of these cultural tensions. It argues that the intensity of the conflict was fueled by widespread misunderstandings, mutual hostilities, and the era’s increasing openness to new social and political ideas. Understanding these factors is essential for comprehending the broader historical and ideological shifts of the era.
Keywords: culture; 1960s; Vietnam War; American; Music; Culture Wars; Protest; Student Movements